2009
DOI: 10.1158/0008-5472.sabcs-903
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab (BV) maintenance therapy significantly delays disease progression (PD) or death compared with placebo (PL) in the AVADO trial (BV + docetaxel [D] vs D + PL in 1st-line HER2-negative locally recurrent [LR] or metastatic breast cancer [mBC]).

Abstract: #903 Background: BV (Avastin®) is a monoclonal antibody to VEGF that significantly improved PFS and response rate when combined with 1st-line taxane chemotherapy (CTx) in two randomised phase III studies in patients (pts) with LR or mBC: E2100 (weekly paclitaxel ± BV) and double-blind, PL-controlled study AVADO (D ± two different BV doses). Preclinical data suggest that BV inhibits tumour neovascularisation and can limit tumour vascular regrowth. Both above trial protocols recommended BV use unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Preclinical studies have demonstrated rapid revascularization following early discontinuation of anti-VEGF treatment which might lead to re-growth of the tumor. Moreover, an exploratory analysis of the AVADO trial showed that maintenance use of bevacizumab after the discontinuation of docetaxel delayed progression of the disease, compared with placebo maintenance treatment [26].…”
Section: Clinical Efficacy In Chemotherapy-naïve Patientsmentioning
confidence: 99%
“…Preclinical studies have demonstrated rapid revascularization following early discontinuation of anti-VEGF treatment which might lead to re-growth of the tumor. Moreover, an exploratory analysis of the AVADO trial showed that maintenance use of bevacizumab after the discontinuation of docetaxel delayed progression of the disease, compared with placebo maintenance treatment [26].…”
Section: Clinical Efficacy In Chemotherapy-naïve Patientsmentioning
confidence: 99%
“…Based on the results from the AVADO trial, the existing EU label permitting the use of bevacizumab in combination with docetaxel was extended to allow bevacizumab to be combined with docetaxel, thus allowing additional patients access to bevacizumab treatment. Further analyses of the AVADO trial have revealed that treatment continuation with singleagent bevacizumab after discontinuation of docetaxel appears to delay disease progression [154], that there is no apparent correlation between the efficacy of bevacizumab plus docetaxel and hypertension or G-CSF use [155], and that the combination does not appear to be associated with a higher incidence of grade 3-5 bleeding events [156]. In summary, although bevacizumab has shown little activity as a single agent in MBC patients, combination therapy with chemotherapeutic agents has been associated with clinical activity in this patient population.…”
Section: Extracellular Targeted Therapies: Monoclonal Antibodiesmentioning
confidence: 99%
“…fined. However, there is some evidence that the combination with the respective cytostatic agent should be switched to maintenance therapy with the VEGF antibody after 6-8 cycles, depending on the remission dynamics [7].…”
Section: Poly(adp-ribose) Polymerase Inhibitionmentioning
confidence: 99%